The Relationship Between Nurses' Knowledge and the Ability to Read ECG to Prevent Cardiac Arrest in the ICU and CCU - Satria, Orita; Apriani, Fitri; Nasution, Nurromsyah; Rahmita Sari, Ika (Institute Of Computer Science (IOCS), 2025)
ECG is a test performed to monitor the electrical activity of the heart muscle. The heartbeat is normal, slow, fast, or irregular. So, to find out the heart rhythm we must be able to read an ECG (Electrocardiogram). To analyze the Relationship between Nurses' Knowledge and the Ability to Read ECGs to Prevent Cardiac Arrest in the ICU and CCU of Cut Nyak Dhien Hospital. This type of quantitative research uses a cross-sectional study design. The study was conducted from April 25 to 30, 2024. The sampling technique was a total sampling of 38 nurses in the ICU and CCU at Cut Nyak Dhien Hospital. Data collected using a questionnaire and analyzed using the Chi-square test. Knowledge with the ability to read ECGs was mostly in the sufficient category, as many as 17 respondents (44.7%). The results showed a relationship between nurses' knowledge and the ability to read ECGs to prevent cardiac arrest with a p value of 0.000 <0.05. It is expected that the hospital can improve nurses' insight and knowledge about ECG through health seminars and special heart training. By increasing nurses' knowledge in reading ECG, the survival rate of heart patients can be increased.